Partial purification and biochemical characterization of a new highly acidic NYSO laccase from Alcaligenes faecalis - Soad A. Abdelgalil; Ahmad R. Attia; Reyed M. Reyed; Nadia A. Soliman (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Due to the multitude industrial applications of ligninolytic enzymes, their demands are increasing. Partial purification and intensive characterization of contemporary highly acidic laccase enzyme produced by an Egyptian local isolate designated Alcaligenes faecalis NYSO were studied in the present investigation. Results Alcaligenes faecalis NYSO laccase has been partially purified and intensively biochemically characterized. It was noticed that 40–60% ammonium sulfate saturation showed maximum activity. A protein band with an apparent molecular mass of ~ 50 kDa related to NYSO laccase was identified through SDS-PAGE and zymography. The partially purified enzyme exhibited maximum activity at 55 °C and pH suboptimal (2.5–5.0). Remarkable activation for enzyme activity was recognized after 10-min exposure to temperatures (T) 50, 60, and 70 °C; time elongation caused inactivation, where ~ 50% of activity was lost after a 7-h exposure to 60 °C. Some metal ions Cu2+, Zn2+, Co2+, Ni2+, Mn2+, Cd2+, Cr2+, and Mg2+ caused strong stimulation for enzyme activity, but Fe2+ and Hg2+ reduced the activity. One millimolar of chelating agents [ethylenediamine tetraacetic acid (EDTA), sodium citrate, and sodium oxalate] caused strong activation for enzyme activity. Sodium dodecyl sulfate (SDS), cysteine-HCl, dithiothreitol (DTT), β-mercaptoethanol, thioglycolic acid, and sodium azide caused strong inhibition for NYSO laccase activity even at low concentration. One millimolar of urea, imidazole, kojic acid, phenylmethylsulfonyl fluoride (PMSF), H2O2, and Triton X-100 caused activation. The partially purified NYSO laccase had decolorization activity towards different dyes such as congo red, crystal violet, methylene blue, fast green, basic fuchsin, bromophenol blue, malachite green, bromocresol purple eriochrome black T, and Coomassie Brilliant Blue R-250 with various degree of degradation. Also, it had a vast range of substrate specificity including lignin, but with high affinity towards p-anisidine. Conclusion The promising properties of the newly studied laccase enzyme from Alcaligenes faecalis NYSO strain would support several industries such as textile, food, and paper and open the possibility for commercial use in water treatment. It will also open the door to new applications due to its ligninolytic properties in the near future.